2013
DOI: 10.1016/j.rmed.2013.05.004
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis on the prophylactic use of macrolide antibiotics for the prevention of disease exacerbations in patients with Chronic Obstructive Pulmonary Disease

Abstract: Prophylactic macrolides are an effective approach for reducing incident COPD exacerbations. There were several limitations to this study including a lack of consistent adverse event reporting and some degree of clinical and statistical heterogeneity between studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
1
8

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 18 publications
0
27
1
8
Order By: Relevance
“…Participants in the SBHR coincided in their use of oral and inhaled antibiotics to treat CBC in patients with BE related to COPD, even though these treatment regimens are not included in the COPD treatment guidelines [36]. The effectiveness of long-term macrolides has been evaluated in COPD and BE with favourable results [37,38] but the use of other oral antibiotics to avoid exacerbations in COPD has had highly variable results: consequently, the systematic use of such drugs is not recommended at this time [39,40]. Only two studies have evaluated the use of inhaled antibiotics—tobramycin and levofloxacin—in a few COPD patients, with inconclusive results [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Participants in the SBHR coincided in their use of oral and inhaled antibiotics to treat CBC in patients with BE related to COPD, even though these treatment regimens are not included in the COPD treatment guidelines [36]. The effectiveness of long-term macrolides has been evaluated in COPD and BE with favourable results [37,38] but the use of other oral antibiotics to avoid exacerbations in COPD has had highly variable results: consequently, the systematic use of such drugs is not recommended at this time [39,40]. Only two studies have evaluated the use of inhaled antibiotics—tobramycin and levofloxacin—in a few COPD patients, with inconclusive results [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, macrolide antibiotics have been explored in several clinical trials for their effects on patients with CLD, including COPD, asthma, cystic fibrosis (CF), and non CFbronchiectasis (3,(5)(6)(7)(8)(9)(10)(11)(12)(13). Recently, several meta-analyses collected the data and confirmed that the long-term use of macrolides improves the quality of life of CLD patients by improving lung function and decreasing the frequency of acute exacerbations (14,15). However, no study has focused on their detrimental effects, especially on microbiological aspects.…”
mentioning
confidence: 99%
“…107,108 It is important to draw attention to the heterogeneity of the antibiotic regimens and the background inhalation therapy evaluated in studies included in the meta-analysis (<50% of patients received double or triple therapy). 107,108 It is important to draw attention to the heterogeneity of the antibiotic regimens and the background inhalation therapy evaluated in studies included in the meta-analysis (<50% of patients received double or triple therapy).…”
Section: Summary Of the Evidencementioning
confidence: 99%